Prognostic Value of Lactate Levels in Trauma Patients’ Outcomes in Emergency Department - sayyed majid sadrzadeh; Vahid Talebzadeh; Seyed Mohamad Mousavi; Behrang Rezvani Kakhki; elnaz vafadar moradi; Hamideh Feiz Disfani (Bulletin of Emergency and Trauma)
Objectives: This study aimed to investigate the prognostic role of lactate clearance in predicting outcomes among trauma patients admitted to the emergency department.Methods: This retrospective cohort study was conducted on patients referred to the Emergency Department. Serum lactate levels were measured at admission and 2 hours later. The patients were followed up for 72 hours to assess outcomes, including discharge, hospitalization in other wards, and mortality.Results: The results showed a significant difference between the mean age, Glasgow Coma Scale (GCS), systolic blood pressure (SBP), pulse rate (PR), and oxygen saturation (O2 Sat) of the trauma patients in relation to mortality prognosis (p<0.05). Additionally, significant differences were found in primary lactate, lactate levels two hours post-admission, and lactate clearance levels based on the patient’s prognosis (p<0.01). Multivariate logistic regression analysis revealed that lactate clearance was associated with a reduced mortality rate among trauma patients (OR=0.907, p<0.05).Conclusion: The findings of this study showed that lactate clearance, as an independent predictive factor, was associated with poorer prognosis and increased mortality rates in trauma patients.